Price Liberalization in Russia : Behavior of Prices, Household Incomes, and Consumption During the First Year - Phillips, Steven (Occasional Papers; Occasional Paper ;, 1993)
Prices in the Russian Federation have been decontrolled in several steps since early 1991, after decades of near fixity. This paper documents and analyzes the behavior of prices, income, consumption, and savings before and after the January 1992 price liberalization, with emphasis on developments during 1992, and with focus on households more than on enterprises. Comparisons are made with recent experience in Central and Eastern Europe, along with consideration of evidence on shortages and income distribution.